Treatment of pediatric rhinosinusitis based on classification of severity - Matsubara, Shigenori (Pediatric Otorhinolaryngology Japan, 2008)
We used a scoring system based on the clinical symptoms of acute pediatric rhinosinusitis (rhinorrhea, postnasal drip, nasal obstruction, bad mood, and productive cough) and intranasal findings (mucopurulent rhinorrhea and/or postnasal drip, serous rhinorrhea and/or postnasal drip, swelling and reddening of nasal mucosa) to study a possible severity classification system. Subjects were 50 pediatric patients suffering from acute rhinosinusitis with mucopurulent rhinorrhea visiting our clinic from November 1 to 13,2007. Although antibiotics should not be used for mild cases of acute pediatric rhinosinusitis, children attending kindergarten or nurseries often required treatment with antibiotics. Many children with moderate cases of acute pediatric rhinosinusitis were improved [almost cured] by administration of the usual dose of antibiotics. Administration of a high dose of antibiotics from the beginning is considered desirable in severe cases. Classification of the severity using a scoring system allowed objective evaluation of the clinical course of acute pediatric rhinosinusitis. Moreover, the results support the view that group care is one risk factor for the development of acute pediatric rhinosinusitis.